Simulation of energy consumption for the heating of an experimental housing module located at 4500 msnm - Ratache Rojas, Pablo Ronel (2021)
In the present work, the energy demand is simulated for an experimental housing module built in the village of Imata, Peru, located at 4500 masl. Prior, the temperature measurements and the energy calculations necessary to validate the simulation model with the program EnergyPlus were performed. To maintain a neutral temperature of 12 ° C in July and 15 °C in December, the simulation indicated that 3,54 MWh are needed yearly, with a daily maximum of 11 kWh in July and a daily minimum of 8,4 kWh in December (monthly averages).